Análise de resistência ao desgaste em aço 15-5PH nitretado a plasma - Fedalto, Marcello (2019)
The study material of this work was stainless steel 15-5PH, which has high mechanical strength and corrosion. To further enhance these characteristics, thermochemical treatment of plasma nitriding is commonly performed. In this work the wear resistance study of this material was carried out, in order to determine the time and temperature of plasma nitriding to give better results in this aspect. For this, samples and some results (core hardness and composite layer, microhardness profile of the nitrided layer, in others) were used in the dissertation of Prof. Dr. Euclides Alexandre Bernardelli, who performed the nitriding for times of 2.4 and 6 hours and temperatures of 663, 713 and 763K, and the sample at 713K was only analyzed with 4 hours of nitriding. This study was also based on the elaboration of Scratch Test in the nitrided and supply state samples in order to determine the critical load, coefficient of friction, worn volume, abrasion factor and 3D and 2D profiles of the grooves of scanning through optical interferometry and scanning electron microscopic analysis. Regarding the results, it was obtained that, except for the sample with less time and temperature of treatment, all the nitrided samples obtained better results of wear in relation to the supply. With the evolution of time and temperature of nitriding the mechanisms of wear evolved from plastic deformations and adhesion to cutting.